Effect of Axonal Trauma on Nerve Regeneration in Side-to-side Neurorrhaphy: An Experimental Study. Issue 12 (December 2016) - Rönkkö, Henrikki; Göransson, Harry; Taskinen, Hanna-Stiina; Paavilainen, Pasi; Vahlberg, Tero; Röyttä, Matias
Abstract : Background: Side-to-side (STS) neurorrhaphy can be performed distally to ensure timely end-organ innervation. It leaves the distal end of the injured nerve intact for further reconstruction. Despite encouraging clinical results, only few experimental studies have been published to enhance the regeneration results of the procedure. We examined the influence of different size epineural windows and degree of axonal injury of STS repair on nerve regeneration and donor nerve morbidity. Methods: Three clinically relevant repair techniques of the transected common peroneal nerve (CPN) were compared. Group A: 10-mm long epineural STS windows; group B: 2-mm long windows and partial axotomy to the donor tibial nerve; and group C: 2-mm long windows with axotomies to both nerves. Regeneration was followed by the walk track analysis, nerve morphometry, histology, and wet muscle mass calculations. Results: The results of the walk track analysis were significantly better in groups B and C compared with group A. The nerve fiber count, total fiber area, fiber density, and percentage of the fiber area values of CPN of the group C were significantly higher when compared with group A. The wet mass ratio of the CPN-innervated anterior tibial muscle was significantly higher in group C compared with group A. The wet mass ratio of the tibial nerve–innervated gastrocnemial muscle was higher in group A compared with the other groups. Conclusions: All three variations of the STS repair technique showed nerve regeneration. Deliberate donor nerve axotomy enhanced nerve regeneration. A larger epineural window did not compensate the effect of axonal trauma on nerve regeneration.